PENGARUH DAN HUBUNGAN PERILAKU PETERNAK TERHADAP TINGKAT ADOPSI INSEMINASI BUATAN PADA SAPI POTONG - Wely Yitro Pello; Cokorda Bagus Darma Putra Mahardika (Politeknik Pertanian Negeri Kupang, 2020)
The success of artificial insemination is not only a factor of feed, seeds and environment but also the quality of human resources. It depends not only from the inseminators but also on farmers’ behaviours as main actors in artificial insemination, which are knowledge, attitudes, and skills. The research was conducted at Amarasi sub-district, aiming to determine the level of farmers’ adoption of artificial insemination, and the effect of farmers’ behaviors on the adoption rate of artificial insemination in beef cattle. The sampling method was purposive sampling, the number of respondents was 40 breeders, data were analyzed descriptively. The effect of farmers’ behavior on adoption rates, the analysis used was multiple linear regression. The relationship between knowledge and adoption rate was a positive and close relationship (rs= 0.715), attitude and adoption rate was a positive relationship (rs= 0.693), skills were positively related to moderate closeness (rs= 0.450), with the adoption rate. Key words: Behaviour, Adoption, Artificial Insemination, Farmers, Beef Cattle.